2022
DOI: 10.1111/tan.14595
|View full text |Cite
|
Sign up to set email alerts
|

The deadly face of felid killer cells: The cytotoxic proteins and their genes

Abstract: Natural killer cells and cytotoxic T lymphocytes are the main cell populations of the immune system able to directly kill target cells via cytotoxic granules. Different mammalian species may differ in specific features of their pore‐forming protein (perforin) and granule‐bound serine proteases (granzymes). One perforin gene (PRF1) and four genes encoding granzymes A, B, H, and K (GZMA, GZMB, GZMH, GZMK) were identified in the reference genomes of felids. The objective of this work was to characterize the genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Our study also clearly demonstrated the importance of the GZMA gene for cats. Taken together, our study and previous studies [6,7,30,31] indicate that there are important immune system differences between pet cats and dog species, although not between breeds and related species. While stray dogs gain an immunological advantage in the fi ght against diseases [30], the opposite is true for cats: owned cats gain an immunological advantage compared to stray cats.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our study also clearly demonstrated the importance of the GZMA gene for cats. Taken together, our study and previous studies [6,7,30,31] indicate that there are important immune system differences between pet cats and dog species, although not between breeds and related species. While stray dogs gain an immunological advantage in the fi ght against diseases [30], the opposite is true for cats: owned cats gain an immunological advantage compared to stray cats.…”
Section: Discussionsupporting
confidence: 80%
“…In another study examining 17 different felid species, nucleotide sequences of PRF1, GZMA and GZMB showed high similarities. All trees derived from coding sequences expressed phylogenetic relationships corresponding to the zoological taxonomy of the Felidae, except GZMA [6]. Bubenikova et al [31] found no signifi cant differences between different cat breeds for PRF1, GZMA, and GZMB genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GZMB can also be produced and released by NK cells. 59 Moreover, neutrophils and T cells are known to release other proteases, such as MMP9 and MMP2, that contribute to BBB damage and dysfunction. 48,49 Employing specific knock-out mice for GZMB or NE will help address this scientific question.…”
Section: Discussionmentioning
confidence: 99%